2001
DOI: 10.1007/s005200000195
|View full text |Cite
|
Sign up to set email alerts
|

Major depression and demoralization in cancer patients: diagnostic and treatment considerations

Abstract: Major depression and demoralization are very common in patients with cancer. A discussion of the diagnostic specificity of major depression and demoralization (also known as adjustment disorder) is presented here, followed by a review of some effects of comorbid depression and cancer. Finally, there are a brief review of studies of antidepressant pharmacotherapy in cancer patients, a treatment algorithm for antidepressant therapy, and suggestions for treatment of demoralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 39 publications
3
59
0
6
Order By: Relevance
“…Clarke and colleagues, using latent trait analysis, found that the dimension of demoralization can be separated from that of anhedonic depression 42,43 . Similar observations have been made with cancer patients 30 . In a study of monozygotic twins discordant for a lifetime history of major depression, one of the three clusters of variables that were significantly different between affected and non-affected twins included higher scores in the twins with major depression in "acting out", in alcohol dependence and in attributes that may be viewed as surrogate (proxy) indicators of SI-helplessness, such as powerlessness, lack of self-efficacy, and a diminished self-perceived sense of mastery 44 .…”
Section: Major Depressive Disordersupporting
confidence: 86%
See 1 more Smart Citation
“…Clarke and colleagues, using latent trait analysis, found that the dimension of demoralization can be separated from that of anhedonic depression 42,43 . Similar observations have been made with cancer patients 30 . In a study of monozygotic twins discordant for a lifetime history of major depression, one of the three clusters of variables that were significantly different between affected and non-affected twins included higher scores in the twins with major depression in "acting out", in alcohol dependence and in attributes that may be viewed as surrogate (proxy) indicators of SI-helplessness, such as powerlessness, lack of self-efficacy, and a diminished self-perceived sense of mastery 44 .…”
Section: Major Depressive Disordersupporting
confidence: 86%
“…The distinction between "distress" and "demoralization" is at the center of a debate whether demoralization is a "normal" (i.e., non-pathological) or homeostatic (and, therefore, not requiring any intervention) or "abnormal" (i.e., pathological) reaction to adversity [29][30][31] . In a community-based sample, the prevalence of demoralization as measured by DCPR was far less frequent than the rates found among medically ill patients, suggesting that demoralization does not simply identify generic psychological distress 32 .…”
Section: Passing or Transient Distress Or Non-specific Distressmentioning
confidence: 99%
“…Several studies confirmed a high prevalence of demoralization among patients with medical disorders, especially with life-threatening or disabling disorders [1][2][3][4][5][6][7] . Demoralization was also found to precede the onset of serious diseases, such as cancer, ischemic heart disease and stroke 1,6,8 .…”
Section: Introductionmentioning
confidence: 92%
“…Mashhadi et al studied 400 patients with cancer after diagnosis of malignancy and before chemotherapy or radiotherapy and reported the prevalence of depression as 26.5% (17). Therefore, due to the high prevalence of depression in patients with cancer and its effects on cancer and disease process and response to treatment, researchers suggested experts and physicians to use counseling sessions and antidepressants drug as one of the main components of treatment for patients with cancer (18,19).…”
Section: Introductionmentioning
confidence: 99%